2015
DOI: 10.1016/j.celrep.2015.03.049
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota of Rural Papua New Guineans: Composition, Diversity Patterns, and Ecological Processes

Abstract: Although recent research revealed an impact of westernization on diversity and composition of the human gut microbiota, the exact consequences on metacommunity characteristics are insufficiently understood, and the underlying ecological mechanisms have not been elucidated. Here, we have compared the fecal microbiota of adults from two non-industrialized regions in Papua New Guinea (PNG) with that of United States (US) residents. Papua New Guineans harbor communities with greater bacterial diversity, lower inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
439
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(487 citation statements)
references
References 50 publications
36
439
3
9
Order By: Relevance
“…This suggests there may be a broader role for maintaining keystone gut microbial genetic and functional diversity in the conservation of NHPs, although further research is needed to determine which microbiome perturbations represent dysbiosis, and which are merely benign or even beneficial adaptations to changes in lifestyle and diet. Previous studies have shown that changes in diet are directly associated with shifts in gut microbial community structure (18,20,34). By leveraging our study design and zoological medical records, we were able to rule out geography, host genetics, antibiotics exposure, and birth in captivity as the primary determinants of the captive primate microbiome.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This suggests there may be a broader role for maintaining keystone gut microbial genetic and functional diversity in the conservation of NHPs, although further research is needed to determine which microbiome perturbations represent dysbiosis, and which are merely benign or even beneficial adaptations to changes in lifestyle and diet. Previous studies have shown that changes in diet are directly associated with shifts in gut microbial community structure (18,20,34). By leveraging our study design and zoological medical records, we were able to rule out geography, host genetics, antibiotics exposure, and birth in captivity as the primary determinants of the captive primate microbiome.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have shown that modern humans have lost a substantial portion of their natural microbial diversity (34)(35)(36). Given the massive loss of gut microbiome diversity in captive primates in this study, captive NHPs may provide an informative model for understanding the effects of modernization and mass human migration on the development of human diseases linked to diet and the microbiome, such as obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was employed by Rampelli et al [3] for studying the effect of urbanization on the gut microbiome and by authors of other previous metagenomic investigations. In particular, the seminal work by De Filippo et al [4] focused on children from Europe and rural Africa and was followed by a larger study [5] encompassing non-urban settings in both the African and South American continents; more recently, several other rural and non-urbanized populations have been surveyed [6,7]. These investigations consistently found that the composition of the intestinal microbiome is clearly different between urbanized populations eating a high-fat diet and rural populations eating a low-fat diet, and that westernization is associated with a loss of microbial diversity including organisms able to ferment fiber-rich dietary components (see Figure 1 for our summary of these data on the bacterial tree of life).…”
mentioning
confidence: 99%
“…The idea that commensal microbes in the gut need to be encouraged, not destroyed (3), has led to the topic becoming mainstream and inspiring high street books such as 'Let Them Eat Dirt' (4) . There is now a prevailing belief in a causal link between ill-health and unbalanced gut flora (5) , and the probability that it is Western lifestyles that are affecting the composition and diversity of the gut microbiota leading to many chronic health problems (6) . Yet despite the rapid rise in allergy related skin-health problems in the developed world (7) , parallel research into the role of the skin microbiome and the body's immune system responses on overall health has been very limited.…”
Section: Skin Immune Systemmentioning
confidence: 99%